Pragmatic pilot cluster randomised control trial of a school-based peer-led anti-smoking intervention for 13-14 year olds in Malaysia: Process evaluation. Issue 6 (2nd October 2017) - Melson, Elniee; Bridle, Christopher; Markham, Wolfgang
Abstract : Purpose: The purpose of this paper is to report the process evaluation of a pilot randomised control trial of an anti-smoking intervention for Malaysian 13-14-year olds, conducted in 2011/2012. It was hypothesised that trained peer supporters would promote non-smoking among classmates through informal conversations. Design/methodology/approach: Smoking-related baseline and follow-up questionnaires were administered, seven months apart, to Form 1 students ( n =2, 118) attending eight schools across two districts in Sabah (Kota Kinabalu; Keningau). Concealed stratified randomisation assigned two schools per district to the control and intervention arms. Control schools received usual care. Intervention schools received usual care and the peer supporter intervention. Peer supporters completed smoking-related knowledge and attitudes questionnaires before and after peer supporter training and peer supporter training evaluation questionnaires. They also discussed the peer supporter training and role in focus groups immediately following training ( n =4) and three months later ( n =3), and additionally, recorded post-training anti-smoking activity in diaries. Findings: The pilot trial found that student recruitment was high (baseline students matched at follow-up n =1, 681 (79 per cent of class-registered students). More boys ( n =38) than girls ( n =35) attended peer supporter training. Post-training, most peer supporters had improved smoking-related knowledge ( n =55; 75 per cent) and attitudes ( n =57; 78 per cent) and returned diaries ( n =49; 67 per cent). Some focus group boys reported they were reluctant peer supporters and/or found resisting smoking difficult. Practical implications: Future trials would benefit from outlined modifications to peer supporter selection, recruitment and training and additionally, assessments of context and intervention acceptability and reach. Originality/value: Trials of complex public health interventions are scarce in economically developing countries.